Osteo-taxonomic distinction of fishes of the family Leiognathidae - James, P.S.B.R. (Indian Journal of Fisheries, 2011)
The subtle external taxonomic differences between closely resembling species of Leiognathidae have been osteologically substantiated by highlighting the differences in the skull bones. Amongst them, the vomer, epiotic, basisphenoid and palatine were found to be characteristic of most of the species.